2013
DOI: 10.1002/jbm.a.34622
|View full text |Cite
|
Sign up to set email alerts
|

Embossing of micropatterned ceramics and their cellular response

Abstract: The aim of this work is to investigate the use of microtopographies in providing physical cues to modulate the cellular response of human mesenchymal stem cells on ceramics. Two microgrooved patterns (100 μm/50 μm, 10 μm/10 μm groove/pitch) were transcribed reversely onto alumina green ceramic tapes via an embossing technique followed by sintering. Characterization of the micropatterned alumina surfaces and their cellular response was carried out. Spread and polygonal cell morphologies were observed on the wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 50 publications
(91 reference statements)
1
25
1
Order By: Relevance
“…Nadeem et al. investigated the effects of micropatterned surfaces on cell responses. These authors created different sized microgrooves (100 μm/50 μm, and 10 μm/10 μm groove/pitch) on ceramic disks, which were then seeded with human mesenchymal stem cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nadeem et al. investigated the effects of micropatterned surfaces on cell responses. These authors created different sized microgrooves (100 μm/50 μm, and 10 μm/10 μm groove/pitch) on ceramic disks, which were then seeded with human mesenchymal stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that cultured human osteoblasts preferred surfaces with relatively high microroughness, which generated increased cell activity. Nadeem et al 2013 investigated the effects of micropatterned surfaces on cell responses. These authors created different sized microgrooves (100 lm/50 lm, and 10 lm/10 lm groove/pitch) on ceramic disks, which were then seeded with human mesenchymal stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…18 In vitro stem cell co-cultures allow observation of the complex interactions between BMSC and BMHC and provide the most accurate model for assessing biomaterials and their effect on both bone formation and normal bone turnover. 19 Several authors report successful co-cultures of osteoblast cell lines or primary osteoblasts combined with peripheral blood mononuclear cells (PBMC) or isolated monocytes, usually of murine or human origin, cultivated with the addition of macrophage colony-stimulating factor (M-CSF). 2022 Previously, the authors have reported co-cultures based on BMSC.…”
Section: Introductionmentioning
confidence: 99%
“…Also, while structural orthopedic ceramics, such alumina/zirconia, tend to be highly bio-inert, metals such as titanium and its alloys are highly adhesive to cells due to their reactive oxide layers and both these low and high adhesion environments can mask topographical effects. However, recent advancements in pre-sintering embossing of green ceramics have illustrated that groove patterns in alumina with different widths can be used to influence fibrous tissue (narrow width, 20 µm pitch) and hard tissue (150 µm pitch with 100 µm groove/50 µm ridge) growth from human osteoprogenitor cells (Nadeem et al, 2013), similarly to results observed on polymers (Biggs et al, 2008).…”
Section: Perspectives On Cell-materials Interactionsmentioning
confidence: 91%